Autologous tolerogenic dendritic cells derived from monocytes of systemic lupus erythematosus patients and healthy donors show a stable and immunosuppressive phenotype. Issue 4 (23rd August 2017) - Obreque, Javiera; Vega, Fabián; Torres, Andy; Cuitino, Loreto; Mackern‐Oberti, Juan P.; Viviani, Paola; Kalergis, Alexis; Llanos, Carolina
Summary: Systemic lupus erythematosus (SLE) is an autoimmune disease with unrestrained T‐cell and B‐cell activity towards self‐antigens. Evidence shows that apoptotic cells (ApoCells) trigger an autoreactive response against nuclear antigens in susceptible individuals. In this study, we focus on generating and characterizing tolerogenic dendritic cells (tolDCs) to restore tolerance to ApoCells. Monocyte‐derived dendritic cells (DCs) from healthy controls and patients with SLE were treated with dexamethasone and rosiglitazone to induce tolDCs. Autologous apoptotic lymphocytes generated by UV irradiation were given to tolDCs as a source of self‐antigens. Lipopolysaccharide (LPS) was used as a maturation stimulus to induce the expression of co‐stimulatory molecules and secretion of cytokines. TolDCs generated from patients with SLE showed a reduced expression of co‐stimulatory molecules after LPS stimulation compared with mature DCs. The same phenomenon was observed in tolDCs treated with ApoCells and LPS. In addition, ApoCell‐loaded tolDCs stimulated with LPS secreted lower levels of interleukin‐6 (IL‐6) and IL‐12p70 than mature DCs without differences in IL‐10 secretion. The functionality of tolDCs was assessed by their capacity to prime allogeneic T cells. TolDCs displayed suppressor properties as demonstrated by a significantly reduced capacity to induce allogeneic T‐cell proliferation and activation. ApoCell‐loaded tolDCs generated from SLE monocytes have a stable immature/tolerogenic phenotype that can modulate CD4 + T‐cell activation. These properties make them suitable for an antigen‐specific immunotherapy for SLE. Abstract : There is currently no cure for systemic lupus erythematosus (SLE) and available treatments are associated with several adverse events, most of them derived from immunosuppression. In this study we have developed a method to generate autologous tolerogenic dendritic cells loaded with apoptotic cells (Tol‐DCs) for SLE patients and healthy controls. Tol‐DCs show a reduced expression of co‐stimulatory molecules, release low levels of pro‐inflammatory cytokines and have limited ability to induce proliferation and activation of allogeneic T‐cells. These promising results could lay the foundations for developing a cell‐based therapy for SLE, without deleterious effects on the immunity of existing therapies.